IMPROVING THE SUSTAINABILITY OF LIVELIHOOD ASSETS AS A STRATEGY FOR PADDY SELF-SUFFICIENCY: A Case At Rural Hoeseholds In Indonesia - Silvana Maulidah, Djoko Koestiono, Fitria Dina Riana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Understanding the importance of a concept of livelihood assets is a way to realize food sovereignty. Development policy formulation is directed towards improving the sustainability of rural communities’ livelihoods. Indonesia as a country with a large portion of its population as rice consumers has established a special program for food security through mobilizing strategic sectors of the domestic agricultural economy. The purpose of this study is to determine the rice self-sufficiency strategy by increasing the sustainability of the livelihood assets of rural communities. The respondents of this study are rural households in the area of rice production centers in Indonesia. The selection of research locations was determined purposively based on the largest rice producing center in East Java Province, that is Malang Regency, Pasuruan Regency and Madiun Regency. The construction of the strategy model is obtained through a quantitative approach: SEM-PLS (Structural Equation Modeling - Partial Least Square) analysis. The results of the study indicate that in the context of creating rice self-sufficiency, it is necessary to increase the sustainability of community livelihood assets: Natural Assets (X2), Financial Assets (X3), and Physical Assets (X4)